Multifocal Medulloblastoma in an Adult Patient: Description of a Rare Presentation and Review of the Literature. (12th September 2020) - Troncon, Irene; Guerriero, Angela; Rossi, Sabrina; Ronzon, Monica; Padovan, Marta; Mario, Caccese; Zanatta, Lucia; Toffolatti, Luisa; Marton, Elisabetta; Lombardi, Giuseppe; Dei Tos, Angelo Paolo; Canova, Giuseppe
Abstract : Medulloblastoma is an embryonal neuroepithelial tumor that affects mainly childhood and more rarely adults. Medulloblastoma occurring as multiple nodules at diagnosis is a rare and tricky presentation. Here, we describe the case of a previously healthy 47-year-old woman with multiple posterior fossa cerebellar tumors. Histological, immunohistochemical, and molecular analyses were performed to best characterize the two excised lesions. The histopathological analysis revealed different variants of medulloblastoma in the excised nodules, one being extensive nodularity, rare in adults, and the other desmoplastic/nodular with areas of anaplasia. Immunostains and molecular analysis classified both nodules as SHH medulloblastoma. Adult medulloblastoma is extremely rare. Important differences exist between adult medulloblastoma and medulloblastoma arising in children and infants. Such differences are in location, distribution of histological variants and of molecular subgroups, survival rates, and therapeutic options. An extensive morphological and molecular characterization of such rare tumors is necessary to choice the best-tailored therapy.